Bernie Thiegs preparing insecticide at Dow agricultural laboratory - Dow Chemical Company (1941)
General view of chemist Bernie Thiegs preparing an insecticide intended to combat potato beetles at the Dow Chemical Company's Agricultural Chemical Research and Development Laboratory facilities. Per an article in the August 1941 edition of the Dow Diamond, the department was responsible for studying the diseases of living plants, the effects of parasites, and the study and testing of insecticides, fungicides, and fumigants. As part of that research, chemists like Thiegs were responsible for the small-scale compounding of insecticidal or fungicidal sprays or dusts, which were subsequently field-tested for uniform and effective distribution on foliage using standard equipment.
Keywords: Agricultural chemicals; Employees; Chemical industry; Laboratories; Dow Chemical Company; Corporations; Insecticides; Agricultural chemistry; Scientific apparatus and instruments; Insect pests; Thiegs, Bernie